The black stallion - Farley, Walter 1915- (Random House, 1941)
Pulled to a desert island by a wild black stallion he has freed during a shipwreck at sea, then rescued by a southbound freighter, a seventeen-year-old boy befriends the horse, trains him by night, and rides him to victory in a match race.